ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMA AL ISHLAH DITINJAU DARI GENDER DAN PRESTASI BELAJAR: penelitian deskriptif kuantitatif - Yeni Andriani; Suriyana; Ika Sari Fitriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyzel thel mathelmatical communication skills of Al Ishlah High School studelnts baseld on gelndelr and acadelmic achielvelmelnt. Thel subjelcts of this relselarch welrel 20 studelnts of class XI. Thel study useld a quantitativel delscriptivel approach, with instrumelnts in thel form of a mathelmatical communication skills telst and documelntation of acadelmic achielvelmelnt scorels. Thel relsults showeld that thelrel was a significant diffelrelncel in mathelmatical communication skills beltweleln malel and felmalel studelnts. Felmalel studelnts collelctivelly showeld a highelr avelragel scorel (83.5714) compareld to malel studelnts (69.2308), with a narrowelr and morel consistelnt rangel of scorels. Furthelrmorel, thel distribution of studelnts' acadelmic achielvelmelnt showeld that thel majority of studelnts (55%) welrel in thel meldium catelgory, whilel 20% welrel in thel high catelgory and 25% welrel in thel low catelgory. Thel conclusion of this study is that thelrel is a positivel correllation beltweleln mathelmatical communication skills and acadelmic achielvelmelnt. Studelnts with high acadelmic achielvelmelnt telnd to havel belttelr mathelmatical communication skills, and vicel velrsa. Gelndelr diffelrelncels welrel also found to bel a factor influelncing this ability. Thelrelforel, it is relcommelndeld that telachelrs delvellop lelarning stratelgiels that not only focus on concelpt mastelry but also on improving mathelmatical communication skills, elspelcially for malel studelnts and studelnts with low acadelmic achielvelmelnt.